An Innovative Approach to Environmental Literacy: The Sustainable RADEC Learning Model for Elementary Schools - Hana Lestari; Ima Rahmawati; Mohammad Ali; Wahyu Sopandi; Ana Ratna Wulan (Al Ibtida: Jurnal Pendidikan Guru MI, 2023)
AbstractThis study aims to design and develop an Education of Sustainable Development-oriented RADEC learning design model for enhancing the environmental literacy of elementary school students. The research approach employed consists of four key stages: (1) problem identification, (2) defining various objectives, (3) design and development, and (4) product validation. The research sample was selected using purposive sampling and comprised six elementary school teachers from various grade levels, ranging from grade 1 to grade 6. Data collection involved the use of scaled questionnaires and interviews. The collected data were then analyzed using the Explanatory Sequential Mixed Method. The results indicate that the curriculum design for the ESD-oriented RADEC learning model is suitable for implementation in elementary schools. This conclusion is supported by the mean score of 3.98 and a standard deviation of 0.22, showing a consistent range of responses among experts. In other words, the experts unanimously agree that the product design is appropriate for classroom learning. To further assess the validity of the design, a one-way ANOVA test was conducted to determine if there were significant differences in the opinions of experts across various domains (ESD, RADEC, Environmental Literacy, and Basic Education). The results revealed that the F score and p-value exceeded Î± = 0.05, indicating no significant differences in the perceptions of the experts involved in the study. In summary, the experts reached a consensus that the product design exhibits a high level of feasibility, earning a "proper" rating in each component developed.Keywords: environmental literacy, ESD, RADEC learning model.Â AbstrakPenelitian ini bertujuan mengembangkan model pembelajaran RADEC berorientasi Education of Sustainable Development (ESD) untuk mengembangkan literasi lingkungan siswa sekolah dasar. Penelitian ini menggunakan penelitian design and development. Prosedur Design and Development yang terdiri dari beberapa langkah yaitu : (1) identifikasi masalah, (2) mendeskripsikan berbagai tujuan, (3) rancangan dan pengembangan artefak, (4) uji validasi artefak.Â  Penelitian ini melibatkan enam orang guru sekolah dasar dari kelas 1 sampai 6 dengan teknik purposive sampling. Pengumpulan data dilakukan dengan kuesioner tertutup berskala likert dan wawancara. Data yang diperoleh kemudian dianalisis menggunakan Explanatory Sequential Mixed Method yaitu metode analisis data yang menggunakan analisis data kuantitatif dan kualitatif. Hasil penelitian menunjukkan bahwa desain kurikulum model pembelajaran RADEC berorientasi ESD layak diterapkan di sekolah dasar, hal ini ditunjukkan dari skor mean (3,98) dan standar deviasi (0,22) dengan rentang yang tidak jauh berbeda. Dapat diartikan persepsi ahli bersifat homogen (setuju) bahwa desain produk layak diterapkan dalam pembelajaran di kelas. Selanjutnya dilakukan uji one way ANOVA untuk mengetahui apakah terdapat perbedaan pendapat para ahli yang signifikan dari para ahli (ahli ESD, RADEC, Literasi lingkungan dan Pendidikan Dasar). Didapatkan hasil skor F dan p-value lebih besar dari Î± = 0,05 dari uji tersebut. Hasil ini menunjukkan persepsi para ahli yang terlibat dalam penelitian ini tidak berbeda nyata. Artinya, para ahli sepakat bahwa desain produk yang dikembangkan memiliki kriteria tingkat kelayakan dengan kategori â€œlayakâ€ untuk setiap komponen produk yang dikembangkan.Kata kunci: literasi lingkungan, ESD, model pembelajaran RADEC.